Perilaku Sosial Siswa di Sekolah dan Implikasinya terhadap Pelayanan Bimbingan dan Konseling - Ilham, Rahmat; Ibrahim, Yulidar; Nurfahanah, Nurfahanah (Konselor, 2014)
Adolescences tend to join and interact with their social groups or peer groups better than their parent. Good social behavior provide acceptance in social groups, otherwise improperly social behavior can provoke rejection. This research is purposed to describe student’s social behavior in school in terms of aggression, conformity and nonverbal communication, and its implication to guidance and counseling treatment. This research is descriptive, with research subject of 47 students of VIII and IX class in SMP N 25 Padang. Research finding reveal that social behavior of students in school in term of aggression is unfavorable (58.39%), social behavior of students in school in term of conformity is unfavorable (60.95%), and social behavior of students in school in term of nonverbal communication is unfavorable (63.91%). Overall, the social behavior of students in school is unfavorable (61.56%).